Aplikasi Program Peningkatan Kualitas Kehidupan Kerja (Quality of Work Life) Dalam Upaya Meningkatkan Kinerja Karyawan - Titiek Mulyaningsih (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2012)
A high quality of work life is essential for organizations to continue to attract and retain employees. Quality Of Work Life (QWL) is a process in which organizations recognize their responsibility to develop job and working conditions that are excellent for the employee and organization. The interventions of QWL will effectively utilize the employee potentials by ensuring great participation and involvement of workers. This paper focuses and analyses the application of QWL to improve employee productivity that leads to organization productivity. They are 10 factors of QWL that influence the improvement of employee productivity: (1) attitude; (2) environment; (3) opportunities; (4) nature of job; (5) people);(6) stress; (7) career; (8) challenges; (9) growth and development; (10) risk and compensation